The effect of fertilization and plant protection in sunflower (Helianthus annuus L.) production - Futó, Zoltán (Acta Agraria Debreceniensis, 2019)
Sunflower is the most important oil crop in Europe which is grown on the biggest area of all the oil crops. The area of producing sunflowers in Hungary was changing to 524–704 thousand hectares in the past decade in comparison with approximately 100 thousand hectares in the 1970’s. In our experiment different sunflower hybrids were examined. The doses of fertilizers were the following in 2017 and 2018: 0–30–90–150 kg ha-1 N, 0-50-90-90 kg ha-1 P2O5 and 0–70–110–110 kg ha-1 K2O. Three different treatments of plant protection were used in the experiment to protect them from fungal infections. A rise in the dosage of nitrogen resulted in increasing infection. The biggest fungal infection was identified in 150 kg ha-1 N, 90 kg ha-1 P2O5 and 110 kg ha-1 K2O treatment. The largest infection was measured on plots without plant protection at the highest N doses, both in leaf and disc diseases. We measured the highest 41.25% in 2017 and 53.1% in 2018 Diaporthe helianthi infection, and 24.5% in 2017 and 25.5 % in 2018 Sclerotinia sclerotiorum disc infection in these plots. kg ha-1Average yield was changing between 2.96–4.67 t ha-1 in 2017/2018. The lowest yield was obtained in the absolute control plot (without plant protection and without nutrient) in both years, which was 2.96 t ha-1 in 2017 and 3.14 t ha-1. The yields increased due to growing nutrient supply and excellent plant protection. The highest yields were 3.67 t ha-1 in 2017 and 4.67 t ha-1 in 2018 (150 kg ha-1 N, 90 kg ha-1 P2O5 and 110 kg K2O active substance). Purpose of the experiment at analysing the impact of different treatments on the profitability of sunflower production.